Comprehensive analysis of Dof transcription factors in Dendrobium species and functional characterization of DoDof4 in the accumulation of water-soluble polysaccharides - Xu, Zhangting; Zhang, Guihua; Zheng, Feixiong; Deng, Xiaoji; Sun, Yiming; Teixeira da Silva, Jaime A.; Shen, Xiaoxia; Yu, Zhenming (Frontiers in Plant Science, 2025)
IntroductionDendrobium is a multi-purpose medicinal orchid that grows on the edge of highaltitude cliffs. The content of water-soluble polysaccharides (WSPs), which primarily play a pharmacological role, is the main criterion for evaluating the quality of Dendrobium orchid. Therefore, it is necessary to study the regulatory manner involved in the accumulation of WSPs.MethodsD. officinale were treated with methyl jasmonate (MeJA), and WSPs content was measured at different time points to assess the dynamic accumulation pattern. To clarify the role of one finger (Dof) family genes in the MeJA-mediated WSP metabolic pathway, a bioinformatics analysis identified Dof members in D. huoshanense, D. nobile and D. officinale. Based on expression patterns and co-expression analysis, a regulatory factor, DoDof4 was identified.ResultsIn this study, the elicitation of D. officinale by methyl jasmonate (MeJA) increased WSP production, which was further amplified by extending the treatment period. Analysis of transcriptomic data revealed that members of the DNA-binding with Dof gene family members accounted for 4% of all differentially expressed genes coding for transcription factors, following MeJA induction. To clarify the role of Dof family genes in the MeJA-mediated WSP metabolic pathway, a bioinformatics analysis identified 29, 29 and 22 Dof members in D. huoshanense, D. nobile and D. officinale, respectively and these were divided into four groups. DoDof4 was encoded a 31.16 kDa protein composed of 292 amino acids, and was targeted on chromosome 3. Furthermore, DoDof4 was a typical transcription factor that localized in the nucleus, displayed transcriptional activity and increased the WSPs accumulation. DoDof4 was co-expressed with 15 genes involved in the WSP metabolic pathway, eight of which displayed a positive Pearson's correlation coefficient. Additionally, correlation analysis revealed the possible downstream targets (KM980199 and KP203853) of DoDof4.DiscussionThe results of the present study suggest that DoDof4 acts as an important regulator in the WSPs metabolic pathway, exhibiting potential values for the improvement of WSPs in Dendrobium species.